Determinants of urban-rural differentials in antenatal care utilization in Nigeria - Babalola, Blessing (My University, 2014)
Demographic and public health studies have indicated urban-rural differences in the utilization of antenatal care services. However, factors accounting for the urban-rural differentials in Antenatal Care use are unknown. The study used the 2008 Nigeria Demographic and Health Survey (NDHS) to examine the background factors associated with the urban-rural differences in antenatal care utilization in Nigeria. Findings revealed a strong urban-rural differential in antenatal care utilization. The logistic regression analysis revealed that age, region, women education, religion, distance to health facility, partner’s education, employment status and wealth status were the significant determinants of antenatal care use in the rural areas of Nigeria. For urban women, age, region, women education, distance to health facility, partner’s education, living children and wealth status were the significant determinants of antenatal care use. In the total model, all the background variables except marital status were significantly associated with antenatal care use. The determinants of urban-rural differentials of antenatal care utilization in Nigeria are religion, occupation and number of living children, as religion and occupation were significantly associated with ANC use in the rural area only, while the number of living children was associated with ANC use in the urban areas only. Non-Catholic Christian and Muslim women were 1.32 and 1.28 times respectively more likely to use antenatal care than their Catholic counterparts. Employed rural women were 1.22 times more likely to use antenatal care than unemployed rural women. Urban women who had 1-2 and 3-4 living children were 2.97 and 2.76 times respectively more likely to use ANC compared to urban women without any living children. However, programmes and policies targeted at improving ANC use in the rural areas of Nigeria should involve religious institutions and promote women employment in the rural areas of Nigeria
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Demography and Population Studies, 2013